Hello! And thank you for your question!
First we are going to redo the equation:
<span><span><span>y<span><span>^3</span><span></span></span></span>−3<span>y^<span><span>2</span><span></span></span></span>(3)+3(y)×<span>3<span><span>^2</span><span></span></span></span>−<span>3<span><span>^3</span><span></span></span></span>=0
Then we are going to use Cube of Difference:
0 = (y - 3)^3
That take cube root of both sides:
0 = y - 3
Finally add 3 to both sides:
3 = y
Final Answer:
y = 3</span></span>
Answer: -15. Quotient is the answer from division. If you do -15/-3, you will get 5
Answer:
For number 2 It would be 10x+12=29
For number 3 Try -37 Because i'm ending up with -36
Step-by-step explanation:
If the 2 was outside of the parenthesis you would multiply both numbers in the parenthesis
Answer:
part 1 of the question is d ,and part 2 of the question is b.
Answer:
15.0 units
Step-by-step explanation:
Here, we want to get the distance between the two points as follows;
CD = √(x2-x1)^2 + (y2-y1)^2
So we have;
CD = √(7+8)^2 + (-5+4)^2
CD = √225+ 1 =
CD = √(226
CD = 15.0 units